1997
DOI: 10.1021/ja970375t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the True Product of the Urate Oxidase Reaction

Abstract: The O2-dependent oxidation of urate catalyzed by urate oxidase has been examined in order to identify the immediate product of the enzymatic reaction. Specifically labeled [13C]urates were utilized as substrates, and the time courses were monitored by 13C NMR. On the basis of chemical shift values and 18O labeling, the product of the reaction was identified as 5-hydroxyisourate. This identification was substantiated by calculation of the 13C NMR spectrum of 5-hydroxyisourate using ab initio density functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 38 publications
8
146
0
1
Order By: Relevance
“…Tipton and colleagues have provided details of the urate oxidase-catalyzed reaction (5,6) and subsequently identified a gene for HIUHase from soybean (G. max) (7,8). The 560-aa soybean HIUHase does not share any sequence similarity with PucM, but belongs to family 1 of glycosidase (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tipton and colleagues have provided details of the urate oxidase-catalyzed reaction (5,6) and subsequently identified a gene for HIUHase from soybean (G. max) (7,8). The 560-aa soybean HIUHase does not share any sequence similarity with PucM, but belongs to family 1 of glycosidase (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the ureide pathway, the conversion of uric acid into allantoin was initially thought to involve a single step catalyzed by urate oxidase (E.C. 1.7.3.3; uricase), but recent investigations have revealed that this pathway includes two additional, distinct, chemically labile intermediates: 5-hydroxyisourate (HIU) and 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline (OHCU) (5,6). It is now generally believed that urate oxidase is responsible only for the conversion of uric acid into HIU, and a second enzyme, HIU hydrolase (HIUHase), catalyzes the hydrolysis of HIU into OHCU (7)(8)(9)(10)(11), which is then converted into allantoin via an enzyme-dependent decarboxylation reaction (Scheme 1) (11).…”
mentioning
confidence: 99%
“…The exact catalytic mechanism is still not fully understood, there is no cofactor nor metallic ion, the optimal pH is basic (between 8.5 and 9), and it is known for a long time that the oxygen atoms in H 2 O 2 derive from those of O 2 [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1d). Based on these results, and the observation of 5-hydroxyuric acid in the uric acid degradation pathway (22), metabolite II (TM-HIU) was proposed as the true product of TMU monooxygenase reaction. Metabolite II (TM-HIU) was unstable under the reaction condition and spontaneously converted to TMA (possibly via metabolite III), as is the case in the uric acid degradation pathway (8,31,32).…”
Section: Resultsmentioning
confidence: 94%